Application of Worship Practice to Form Habits at Madrasah Tsanawiyah: Penerapan Pengamalan Ibadah untuk Membentuk Kebiasaan di Madrasah Tsanawiyah - Khariri, Moch Sholakhuddin Al; Romadlon, Dzulfikar Akbar (Universitas Muhammadiyah Sidoarjo, 2023)
When the practice is used to be done thanks to this habit, it will become a habit for those who do it, then it will become addicted and in time it becomes a tradition that is difficult to break. Therefore, this is where the importance of habituation in the educational process. Habituation will form a character, so that later worship will be carried out continuously without any sense of coercion. Like the research conducted by the author at this school. Based on these objectives, this article uses qualitative research methods. This research is intended to raise facts, circumstances, variables, and phenomena that occur. The result of this paper is the implementation of worship at MTs Ma'arif Ketegan Tanggulangin Sidoarjo scheduled with different hours for each grade level. Constraints in the implementation of worship facilities that still use the village mosque which is close to the school. In terms of students, many are still not familiar with the activities in the school environment of MTs Ma'arif Ketegan Tanggulangin Sidoarjo.